Regional cortical thinning and area reduction are associated with cognitive impairment in hemodialysis patients - Hui Juan Chen; Jie Qiu; Yonghui Qi; Yihao Guo; Zhanrong Zhang; Haodong Qin; Feiyun Wu; Feng Chen (Brain Research Bulletin)
Magnetic resonance imaging (MRI) has shown that patients with end-stage renal disease have decreased gray matter volume and density. However, the cortical area and thickness in patients on hemodialysis are uncertain, and the relationship between patients’ cognition and cortical alterations remains unclear. Thirty-six hemodialysis patients and 25 age- and sex-matched healthy controls were enrolled in this study and underwent brain MRI scans and neuropsychological assessments. According to the Desikan-Killiany atlas, the brain is divided into 68 regions. Using FreeSurfer software, we analyzed the differences in cortical area and thickness of each region between groups. Machine learning-based classification was also used to differentiate hemodialysis patients from healthy individuals. The patients exhibited decreased cortical thickness in the frontal and temporal regions, including the left bankssts, left lingual gyrus, left pars triangularis, bilateral superior temporal gyrus, and right pars opercularis and decreased cortical area in the left rostral middle frontal gyrus, left superior frontal gyrus, right fusiform gyrus, right pars orbitalis and right superior frontal gyrus. Decreased cortical thickness was positively associated with poorer scores on the neuropsychological tests and increased uric acid and urea levels. Cortical thickness pattern allowed differentiating the patients from the controls with 96.7 % accuracy (97.5 % sensitivity, 95.0 % specificity, 97.5 % precision, and AUC: 0.983) on the support vector machine analysis. Patients on hemodialysis exhibited decreased cortical area and thickness, which was associated with poorer cognition and uremic toxins.